Evaluation of antibiotic prescribing for the treatment of male community-acquired urinary tract infections using reimbursement data - Adrien Biguenet; Céline Slekovec; Kévin Bouiller; Xavier Bertrand (PLoS ONE, 2025)
Introduction Urinary tract infection (UTI) in men, although less common than in women, present specific diagnostic and therapeutic challenges. This study aims to evaluate the prescribing practices of general practitioners (GPs) for male UTI in France, focusing on adherence to guidelines. Materials and methods We used an anonymous reimbursement database of antibiotics prescribed 15 days around an urine culture between September 2019 and August 2022 in a French region. Antibiotic prescriptions for male UTI were analysed according to adherence to national guidelines. Cluster analysis was used to identify different GP prescribing profiles. Prescription duration was assessed according to the number of antibiotic boxes delivered in the community pharmacy. Results We included 7,816 urine culture prescriptions from 940 GPs for 6,457 male patients. We estimated compliance with French recommendations to be 55.7% for empirical treatment and 68.1% for documented treatment. GPs were divided into three clusters with different adherence to recommendations of 22%, 44% and 77%. Treatment duration for fluoroquinolones and cotrimoxazole was heterogeneous between GPs, but mainly too short. Conclusions Our results suggest that our method could identify GPs who do not prescribe in accordance with recommendations and enable health insurance systems to target educational interventions to improve antibiotic prescribing practices.